Penerapan Metode Show and Tell Untuk Meningkatkan Kemampuan Berbicara Anak Usia 4-5 Tahun - Andini, Yuwandha Styo; Rahmawati, Ida Yeni; Wahyudi, Wahyudi (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Show and Tell is a learning method that aims to develop children's speaking skills and confidence through activities of showing objects and telling stories behind them. This study aims to analyze the implementation of the Show and Tell method in strengthening the speaking skills of 4-5-year-old children at Dharma Wanita 01 Badegan Kindergarten. This study uses a qualitative approach with field research. Data were collected through observation of the implementation of activities, interviews with the principal and classroom teachers, and documentation in the form of activity plans and learning evaluation results. Data validity was obtained through triangulation of techniques and sources. The indicators of speaking skills analyzed included pronunciation, voice volume, word choice, intonation and pauses, fluency, and confidence. The results showed that the application of the Show and Tell method was able to improve children's speaking skills, active participation, and confidence through sharing personal items. This method also strengthened the relationship between home and school and deepened children's understanding of learning materials. Therefore, the application of Show and Tell requires effective planning and classroom management in order to become an optimal learning strategy in stimulating the speaking skills of early childhood.